Peran Dukungan Keluarga dan Konsep Diri Terhadap Peningkatan Keterampilan Sosial Anak Tunarungu di Sekolah Inklusif - Lana Pratiwi Rukmana Sutoyo; Wiwin Hendriani (Faculty of Psychology, Universitas Semarang, 2018)
This research aims to find out whether there is an influence of family support and self-concept on social skills of deaf children in inclusive schools. The data collection tool of this study uses a questionnaire with a family support scale compiled by the author based on the theory of Caplan (1976), the scale of self-concept compiled by the author based on the theory of Caldarella & Merrel (2003). The reliability of the family support scale is 0.913 self-concept scale of 0.969 and the social skill scale is 0.892. Data analysis in this study was carried out by multiple regression techniques. Based on the results of the data analysis, the influence of family support and self-concept on social skills in Deaf children with a significance value of 0,000, R value of 0.983 and R square of 0.966 indicates that the contribution percentage of the variable family support and self-concept is 96.6% while the remaining 3.4% is influenced or explained by other variables that are not used.